Simple approach for the synthesis of Dy2Sn2O7 nanostructures as a hydrogen storage material from banana juice - Zinatloo-Ajabshir, Sahar; Morassaei, Maryam Sadat; Salavati-Niasari, Masoud (Journal of cleaner production, 2019)
In this experimental study, a new green and simple approach has been utilized to prepare nanostructured Dy2Sn2O7 as a remarkable material. It is the first report on the production of pure Dy2Sn2O7 nanostructures with utilizing banana juice as natural reagent as well as Dy3+ and Sn4+ sources. The effects of pressing the reactants within a pellet (in the solid form) and the use of banana in two different forms, in the form of solid powder or juice, as well as the applied amount of banana have been studied to achieve the condition for producing the sample with optimal morphology, purity and size. Various micro/nanostructures could be produced via changing the experimental condition. Based on the findings in this research, utilization of banana juice had remarkable role in Dy2Sn2O7 shape and size. Further, several analyses have been carried out to investigate the purity, porosity, composition and shape of the made samples. In following, for first time, the electrochemical hydrogen storage efficiency of Dy2Sn2O7 produced utilizing banana juice has been studied with chronopotentiometry method. The maximum discharge capacity of Dy2Sn2O7 that produced utilizing banana juice has been 4023 mA h/g after 20 cycles and this mesoporous sample demonstrated very good performance at room temperature. On the basis of the findings, the great discharge efficiency related to the green synthesized Dy2Sn2O7 nanostructures with utilization of banana juice can make them as competitive and desirable materials for hydrogen storage technology that they can bring about the diminution in the environmental contamination. •A new green and simple approach was utilized to prepare Dy2Sn2O7 nanostructures.•Banana juice was applied as new and green fuel.•Various micro/nanostructures could be produced via changing the experimental conditions.•Electrochemical hydrogen storage of Dy2Sn2O7 was examined, for the first time.